MAKNA SIMBOL KOMUNIKASI BUDAYA DALAM GENDUREN MEGENGAN PADA MASYARAKAT DUSUN WALENG GIRIMARTO WONOGIRI - Suryono, Joko; Aji Pamungkas, Bagoes (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2025)
Understanding cultural symbols within a tradition cannot be separated from efforts to preserve its cultural values. Symbols in a cultural context function not only as physical representations or ritual actions, but also as a communication medium that contains the values, beliefs, and worldviews of the community supporting the culture. One tradition that still maintains its cultural symbols is Genduren Megengan. This study aims to examine the meaning of cultural communication symbols in the Genduren Megengan tradition in the Waleng Hamlet community, Girimarto District, Wonogiri Regency. This tradition is part of the cultural heritage of an agrarian society rich in religious, social, and cultural values. This study used a qualitative approach with Clifford Geertz's symbolic interpretation method. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results show that the symbols in the Genduren Megengan tradition were divided into three primary forms: object symbols, verbal symbols, and nonverbal symbols. Each symbol had a religious meaning as a form of respect for ancestors, a social meaning in strengthening relationships between community groups, and a cultural meaning as an effort to preserve local identity. These symbols form a ritual communication that strengthens solidarity and social cohesion within the community. This study concludes that the Genduren Megengan tradition is not only an annual ritual but also a means of cultural communication with profound meaning